Role of family and entrepreneurial leadership development of university students. - Bagheri, Afsaneh; Lope Pihie, Zaidatol Akmaliah (IDOSI Publications, 2010)
Family has been identified as the first place that enhances students’ awareness about, attitude toward and capabilities of entrepreneurship. However, little attentions has been directed to how family nurtures entrepreneurial abilities particularly, the competencies to lead entrepreneurial activities in students. This study aimed to provide a deeper understanding of how family develops entrepreneurial leadership competencies of university students. A total of fourteen student entrepreneurial leaders, defined as students who were highly involved in leading university entrepreneurship clubs and projects, was purposefully selected and interviewed. Half of the students had one of their parents as an entrepreneur and the parents of the half were not involved in entrepreneurship. Analysis of the data revealed that parents played an influential role in inspiring students to get involved in entrepreneurial activities, whether or not they themselves were entrepreneurs. Furthermore, lived and continuous involvement in family business developed the students’ self-efficacy in leading entrepreneurial activities. The findings are discussed in terms of theoretical and practical implications.